Association of H. pylori gastritis with Non-alcoholic Hepatic Steatosis in Patients - A Cross-Sectional Study in Tertiary Care Hospitals - MARYAM ASHRAF; MUHAMMAD ZAHID ALI RAZA; FAIZA ALTAF; MAIDA ANWAR; ARSALAN ASLAM CHAUDHARY; AAMIR SIDDIQUE (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Helicobacter pylori is a common gastric pathogen that is more and more associated with systemic metabolic disorders. Obesity and insulin resistance are known as conditions that are associated with non-alcoholic hepatic steatosis, or liver fat. Aim: The recent studies suggest the presence of possible correlation of H. pylori gastritis with hepatic fat accumulation. Methodology: Between September to December 2024, this study was conducted in two tertiary care hospitals in Lahore, Pakistan. Upper gastrointestinal endoscopy and abdominal ultrasonography were performed in a total of 100 adult patients with dyspeptic symptoms. A diagnosis of H. pylori infection was confirmed by rapid urease test and histopathology of gastric biopsies and hepatic steatosis was diagnosed based on ultrasounds which were suggestive of a fatty liver. Those who had previously used alcohol, who had viral hepatitis or who had known liver diseases were excluded. Results: Sixty two percent of enrolled patients (n=62) tested positive for H. pylori infection and 48 percent (n=48) had ultra-sonographic evidence of nonalcoholic hepatic steatosis. Of the 35 patients with H. pylori gastritis 56.4% showed concurrent hepatic steatosis as compared to 13 (30.9%) in H. pylori negative patients. This was a statistically significant association (p = 0.012). Patients with both conditions had elevated BMI and fasting blood glucose. Conclusion: The association between H. pylori gastritis and nonalcoholic hepatic steatosis in dyspeptic patients was found in this study. These findings indicate a possibility of a chronic H. pylori infection having an extra-gastric metabolic influence. Longitudinal studies to explore the causal relationship and the underlying pathophysiological mechanisms are recommended further.